Maritime security and technological trends - Alfultis, Michael A. (Revista Científica I+D+i MARÍTIMA, 2018)
This presentation considers how continuous technological change, and the increasing rate of this change, will impact maritime education and training and our graduates. Changes in technology, the environment, the regulatory picture and globalization represent a more complex array of forces for our students to understand than ever before. Students can no longer assume that acquired technical skills will serve the demands of their rapidly changing workplaces. These changes and challenges require maritime universities to elevate our academic programs, ensure our curricula remain relevant, and provide our students with tools and adaptive skill sets they will need to become life-long learners.